Compartmentalized Histoplasma capsulatum Infection of the Central Nervous System - Albert J. Eid; John D. Leever; Kathrin Husmann (Case Reports in Infectious Diseases)
Background. Histoplasmosis is a common fungal infection in the southeastern, mid-Atlantic, and central states; however, its presentation can be atypical. Case Presentation. We report a case of Histoplasma capsulatum infection presenting as slowly progressive weakness in the lower extremities, followed by the development of numbness below the midthoracic area, urinary incontinence, and slurred speech. Brain MRI showed leptomeningeal enhancement, predominantly linear, involving the basal cisterns, the brainstem, and spinal cord. Cerebrospinal fluid analysis showed lymphocytic pleocytosis. Discussion. CNS histoplasmosis is usually seen in patients with disseminated histoplasmosis. Isolated CNS histoplasmosis is rarely seen, especially in immunocompetent patients. Conclusions. Histoplasmosis should be considered in the differential diagnosis of patients experiencing slowly progressive neurological deficit.